A new species of Ephesiopsis (Polychaeta: Sphaerodoridae) from off southeastern Brazil - Rizzo, Alexandra Elaine (Zootaxa, 2009)
Sphaerodorids belonging to the genus Ephesiopsis were collected on the outer continental shelf and slope off the coast of São Paulo State, during the REVIZEE/Score Sul/Benthos Program. Ephesiopsis guayanae Hartman and Fauchald 1971 from off Guyana is the only species previously known in this genus. Ephesiopsis shivae sp. nov., differs from E. guayanae in having a longer body, macrotubercles with smaller terminal papillae, and simple chaetae not as pointed distally; eyes are absent in the new species. Four macrotubercles with terminal papillae were observed on the pygidium of E. shivae sp. nov. Such macrotubercles were not reported in E. guayanae, although the specimens are complete; the presence of these structures in the new species necessitating emendation of the genus diagnosis.